HOW NURSES RESPECT PATIENT'S RIGHTS - Nasiriany, KH; Salemi, S; Salman Yazdy, N; Hosseini, F (Iran University of Medical Sciences, 2002)
Background: Respecting patient's right is what, patients expect from health centers. It means that the patients regardless to their age, sex, race and other differences have some rights such as: knowing, selecting, being respected, confidentiality, territoriality and receiving efficient care and treatment and nurses must respect these rights. Objective: To determine the nurse's level of respect for the patients rights. Design: This was a cross- sectional study in which through two dimensional tools the nurses level of respect for patient's rights determined and measured. Sample: 280 nurses were selected through stratified randomized sampling. Results: The results showed moderate respect for patient's rights. Conclusion: Findings showed moderate respect for patient's rights. It is suggested to provide session of teaching on patient's rights for nurses, and it is also recommended to inform the patients about their own rights. These, consequently lead to a better and qualified patient's care.